BBX17 Interacts with CO and Negatively Regulates Flowering Time in Arabidopsis thaliana. (7th January 2022) - Xu, Xiaorui; Xu, Jingya; Yuan, Chen; Chen, Qianqian; Liu, Qinggang; Wang, Xuming; Qin, Cheng
Abstract: Floral transition, the change from vegetative growth to reproductive development, is dramatic in flowering plants. Here, we show that one subgroup III member of the B-box (BBX) family, BBX17, is a repressor of floral transition under long-day conditions. BBX17 contains a B-box domain and a CCT domain. Although the phenotype of the BBX17 loss-of-function plants was comparable to that of wild-type plants, BBX17 -overexpression plants displayed a delayed-flowering phenotype under long-day conditions. The delayed-flowering phenotype was not the result of an altered CONSTANS ( CO ) expression level but rather the repression of the FLOWERING LOCUS T ( FT ) expression level. BBX17 physically associated with CO and repressed its ability to control FT expression. Furthermore, the BBX17 protein degraded in the dark, but irradiating seedlings with white, blue, red or far-red light stabilized the BBX17 level. We also proved that the degradation of BBX17 was via 26S proteasome and requires COP1. Thus, BBX17 acts as a key factor in the CO–FT regulatory system to control Arabidopsis thaliana flowering.